Species-specific COI primers for rapid identification of a globally significant invasive pest, the cassava mealybug Phenacoccus manihoti Matile-Ferrero - Yu-sheng WANG; Hu TIAN; Fang-hao WAN; Gui-fen ZHANG (Journal of Integrative Agriculture, 2019)
The globally invasive cassava mealybug Phenacoccus manihoti Matile-Ferrero is a pernicious pest of cassava, and its recent introduction into Asia has raised considerable alarm. To slow or prevent further invasion, an accurate, simple, and developmental-stage-independent detection method for P. manihoti is required. In the present study, a PCR method based on a species-specific mitochondrial DNA cytochrome oxidase I (SS-COI) marker was developed for rapid identification of P. manihoti. One pair of SS-COI primers (PMSSZW-1F and PMSSZW-1R) was designed based on sequence variations in the COI gene among P. manihoti and related mealybug species. Specificity of the primer pair was validated on 21 closely related species. Sensitivity tests were performed on four immature developmental stages and female adults. Efficacy tests demonstrated that at the relatively low concentration of (135.2±14.7) pg μL−1 resuspended DNA, the specific fragment was detected in all replicates. Furthermore, the SS-COI primer pair was assayed on three populations of P. manihoti from major exporting countries of cassava. The PCR assay was proved to be a rapid, simple, and reliable molecular measure for the identification of P. manihoti. This tool will be useful for quarantine, monitoring, and management of this invasive pest.